2003
DOI: 10.1002/ajim.10172
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and lung function in health care personnel exposed to glutaraldehyde

Abstract: Further exposure controls for both glutaraldehyde and gloves are required to improve skin care in glutaraldehyde exposed nurses. Exposure monitoring methods also need review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
2
23
1
1
Order By: Relevance
“…In this study, exposure levels sometimes exceeded 0.05 ppm, the threshold limit values recommended by the ACGIH 17) . This study further showed levels of exposure comparable to earlier reports from British and Australian investigators 12,13) . Leinster et al 9) reported concentration levels as high as 0.04 ppm during changeover of glutaraldehyde solutions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, exposure levels sometimes exceeded 0.05 ppm, the threshold limit values recommended by the ACGIH 17) . This study further showed levels of exposure comparable to earlier reports from British and Australian investigators 12,13) . Leinster et al 9) reported concentration levels as high as 0.04 ppm during changeover of glutaraldehyde solutions.…”
Section: Discussionsupporting
confidence: 90%
“…Glutaraldehyde exposure is also associated with various nasal, respiratory, and ocular symptoms Industrial Health 2007, 45, [289][290][291][292][293][294][295] and headache [3][4][5][6][7][8][9][10][11][12] . Exposure to glutaraldehyde has been shown to reduce FVC and FEV 1 among current and ex-employees 12,13) . Allergic contact dermatitis and asthma have been reported among health care professionals from occasional or incidental occupational exposure to glutaraldehyde 11,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether repeated GA exposures actually cause occupational asthma, however, is currently under debate. Although numerous reports of work-related asthma have appeared in the medical literature (42)(43)(44)(45)(46)(47)(48)(49), not all studies have shown a positive correlation with GA exposure (9). Furthermore, although laboratory tests do exist for GA-related IgE, some studies have shown that only a small percentage of subjects with symptoms actually have these specific antibodies (50, 51).…”
Section: Occupational Disorders From Glutaraldehydementioning
confidence: 99%
“…Increasing temperature and solution concentration subsequently increases the vapor pressure of GA mixtures and thus, its environmental concentration. As such, good occupational hygiene principles need to be adopted and (49,57) • Laboratory technicians (33,38) • Contact dermatitis (39)(40)(41) • X-ray technicians (31,32,43,46) • Headache (28,30,43) • Cleaners, veterinarians (39,40,43) Chronic…”
Section: Reducing Occupational Exposurementioning
confidence: 99%